Large-strain, high-stress tubular dielectric elastomer actuator with high pre-stretch and oil encapsulation - Tan, Desmond Di-Teng (2018)
Rolled dielectric elastomer actuators (DEA), which are prepared by rolling up a flat dielectric elastomer , are subjected to non-homogenous deformation and thus does not perform as well as the flat ones. Typically, the rolled ones reported actuation of not more than 37.3% axial strain; whereas the flat one undergoing pure-shear deformation reported much greater actuation . This study shows that oil encapsulation helps the rolled DEA suppress pre-mature breakdown. Under isotonic test, oil-encapsulated tubular DEAs sustain very high electric field of up to 712.0 MV/m, which is 50% higher than that of the dry DEAs. Hence, it can produce up to 50% axial strain while deforming the passive oil capsules. In addition, it produces an isometric stress up to nearly 0.6 MPa, 114% higher than that of the dry one.